Nghiên cứu đặc trưng, các hiện tượng xảy ra trong quá trình điều chế và hoạt tính của xúc tác AuY cho phản ứng oxi hóa hoàn toàn toluen - Huyền, Phạm Thanh; Như Quỳnh, Lê Thị; Tường, Đào Văn (Vietnam Journal of Chemistry, 2014)
Gold catalysts supported on zeolite Y were prepared by ion-exchange. The catalysts were characterized by XRD, TGA/DTA, IR, SEM and TEM. It is shown that gold crystallites are deposited on framework of zeolit and zeolit structure is not deformed after being dried at 110oC and calcined at 400oC. The average size of the gold particles depends on the gold content of the support. The complete oxidation of toluen in air was carried out over AuY. Catalytic activity was tested at temperature of 250 to 400oC. Toluene was converted completely to COx. No organic byproducts were detected. Catalytic activity depends on temperature, gold content and time on stream.